Evaluation of histological changes after tracheal occlusion at different gestational ages in a fetal rat model (Clinics, 2013)
OBJECTIVES: To evaluate the histological changes of tracheal cartilage and epithelium caused by tracheal occlusion at different gestational ages in a fetal rat model. METHODS: Rat fetuses were divided into two groups: a) External control, composed of non-operated rats, and b) Interventional group, composed of rats operated upon on gestational day 18.5 (term = 22 days), divided into triads: 1) Tracheal occlusion, 2) Internal control and 3) Sham (manipulated but not operated). Morphological data for body weight, total lung weight and total lung weight/body weight ratio were collected and measured on gestational days 19.5, 20.5 and 21.5. Tracheal samples were histologically processed, and epithelial, chondral and total tracheal thicknesses were measured on each gestational day. RESULTS: The tracheal occlusion group exhibited an increase in total lung weight/body weight ratio (p